PENGARUH CORPORATE BRANDING TERHADAP KEPUTUSAN PEMBELIAN PADA HOTEL TIRTAGANGGA - Arti Sukmalengkawati; Widiya Siti Safrina (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2021)
Corporate branding is one strategy that companies can use in introducing products. Corporate branding is the application of the company name as a brand that is introduced to consumers. With the use of corporate branding strategy, the company can have a competitive advantage over its competitors. Where consumers can easily identify products owned by the company and are able to gain consumer trust. So that consumers can be helped during the decision-making process to reach a final purchase decision. The research method used is descriptive and associative methods. The analytical method used is normality analysis, product moment correlation analysis, determination analysis, and hypothesis analysis and then processed using SPSS version 25 computer program. The results of this study indicate that the company's branding has an effect on purchasing decisions. This is based on the product moment correlation coefficient of 0.489 and is proven by the results of the coefficient of determination (KD) test of 23.9% that maintenance is able to explain the importance of the production process. The remaining 76.1% is influenced by other factors not examined. Corporate branding is one strategy that companies can use in introducing products. Corporate branding is the application of the company name as a brand that is introduced to consumers. With the use of corporate branding strategy, the company can have a competitive advantage over its competitors. Where consumers can easily identify products owned by the company and are able to gain consumer trust. So that consumers can be helped during the decision-making process to reach a final purchase decision. The research method used is descriptive and associative methods. The analytical method used is normality analysis, product moment correlation analysis, determination analysis, and hypothesis analysis and then processed using SPSS version 25 computer program. The results of this study indicate that the company's branding has an effect on purchasing decisions. This is based on the product moment correlation coefficient of 0.489 and is proven by the results of the coefficient of determination (KD) test of 23.9% that maintenance is able to explain the importance of the production process. The remaining 76.1% is influenced by other factors not examined.